(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This study aimed to explain the Pancasila and the 1945 Constitution noble’s values. Civics as a moral value education requires a humanistic approach and no longer indoctrination which they can build democratic citizens towards civilized society (civil society). The method used descriptive qualitative includes the following steps: (1). observation (2). interview, (3). Content analysis (document analysis), (4). Triangulation. The results showed that the portfolio-based learning model was able to foster a number of citizenship competencies as a whole, namely smart children and citizens as well as participatory and responsible Indonesian citizens.